(untitled) (Alternautas, 2016)
In this introduction, Gerardo Muñoz discusses the question underpinning this dossier, as we seem to witness the crisis of the Latin American progressive cycle. The contributions collected are varied in style and argumentation, as well as in the case studies discussed. Yet, they are not meant to be read as comprehensive reflections on the region throughout these years. Instead, each of the contributions essentially should be read as evoking a paradigm that allows us to rethink a problem or a series of problems that traverse different key sites. These are also conjectural texts, but to the extent that they seek to think through central issues of Latin America politics, they also exceed the established temporal parameters fixed by the ‘untimely present’ or the ‘actual movement’ of contemporaneity. There is a tension throughout across the articles that point to different ways of understanding the ‘crisis’ (which is fundamentally the crisis or krenein of thought, that is, of judgment).